Turning the Orogenic Switch: Slab‐Reversal in the Eastern Alps Recorded by Low‐Temperature Thermochronology - Paul R. Eizenhöfer; Christoph Glotzbach; Lukas Büttner; Jonas Kley; Todd A. Ehlers (Geophysical Research Letters)
Abstract Many convergent orogens, such as the eastern European Alps, display an asymmetric doubly vergent wedge geometry. In doubly vergent orogens, deepest exhumation occurs above the retro‐wedge. Deep‐seismic interpretations depict the European plate dipping beneath the Adriatic, suggesting the pro‐wedge location on the north side of the orogen. Our new thermochronometer data across the Eastern Alps confirm distinct shifts in the locus of exhumation associated with orogen‐scale structural reorganizations. Most importantly, we find a general Mid‐Miocene shift in exhumation (in the Tauern Window and the Southern Alps) and focus of modern seismicity across the Southern Alps. Taken together, these observations suggest a subduction polarity reversal at least since the Mid‐Miocene such that the present‐day pro‐wedge is located on the south side of the Alps. We propose a transient tectonic state of a slow‐and‐ongoing slab reversal coeval with motion along the Tauern Ramp, consistent with a present‐day northward migration of drainage divides.